Enforcement Of Environmental Crimes In Medan City Towards The Impact Of Transition Of Regional Regulation No. 6 Of 2015 - Suwarto, Suwarto; Alsa, Abdul Aziz (PT. Anagata Sembagi Education, 2025)
: The amendment of Regional Regulation (Perda) no. 6 of 2015 on Waste Management in Medan City has implications for law enforcement against environmental crimes. This study aims to analyze how regulatory changes affect the effectiveness of legal sanctions for violators and their impact on more sustainable waste management. This research employs a qualitative method with a juridical-normative approach through legal analysis and interviews with relevant stakeholders. The findings indicate that the amendment strengthens the legal basis for addressing violations, including increased administrative and criminal sanctions for environmental polluters. However, implementation still faces challenges, such as low public awareness and limited resources for law enforcement agencies. Therefore, strengthening synergy between the government, society, and the private sector is necessary to enforce regulations and enhance environmental awareness